1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<274::aid-ijc19>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix metalloproteinase-2 (MMP-2) by hepatocyte growth factor/scatter factor (HGF/SF) in human glioma cells: HGF/SF enhances MMP-2 expression and activation accompanying up-regulation of membrane type-1 MMP

Abstract: Hepatocyte growth factor/scatter factor (HGF/SF) contributes to the malignant progression of human gliomas. We investigated the effect of HGF/SF on matrix metalloproteinase‐2 (MMP‐2), membrane type 1 matrix metalloproteinase (MT1‐MMP) and tissue inhibitors of metalloproteinases (TIMPs), expressions of c‐Met/HGF receptor‐positive human glioblastoma cells. Treatment of U251 human glioblastoma cells with HGF/SF resulted in enhanced secretion of MMP‐2 with an increased level of the active form. This was accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…It has been shown to be highly expressed in high grade bladder tumours using immunohistochemistry (Neal et al, 1990). The Hepatocyte Growth Factor (HGF) receptor c-MET tyrosine kinase is expressed on epithelially derived tumour cells, and is involved in HGF mediated activation of both MMP2 and MT1-MMP (Hamasuna et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be highly expressed in high grade bladder tumours using immunohistochemistry (Neal et al, 1990). The Hepatocyte Growth Factor (HGF) receptor c-MET tyrosine kinase is expressed on epithelially derived tumour cells, and is involved in HGF mediated activation of both MMP2 and MT1-MMP (Hamasuna et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several investigators reported that HGF up-regulated matrix-degrading enzymes. [31][32][33][34] We also reported that the augmentation of HGF/c-met signal upregulated proMMP9, proMMP1, and uPA in a renal cell carcinoma cell line, Caki-1. 18 In this oral SCC cell system, we also examined the effect of HGF on the activity of the gelatinase produced by BHY and HN cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intramyocardial delivery of HGF in mice enhanced migration of c-kit þ CSCs from surrounding myocardium to the infarcted region where they formed new myocytes and improved cardiac contractile function . Interestingly, the effect of HGF on migration of c-kit þ CSCs has been attributed to the expression of matrix metalloproteinases (Hamasuna et al, 1999;Urbanek et al, 2005).…”
Section: Hepatocyte Growth Factor/c-metmentioning
confidence: 99%